2022
DOI: 10.3389/fcimb.2022.803502
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Manipulation of Psychiatric Behavioral Disorders Induced by Toxoplasma gondii

Abstract: Toxoplasma gondii is known to have a complex life cycle and infect almost all kinds of warm-blooded animals around the world. The brain of the host could be persistently infected by cerebral cysts, and a variety of psychiatric disorders such as schizophrenia and suicide have been reported to be related with latent toxoplasmosis. The infected animals showed fear reduction and a tendency to be preyed upon. However, the mechanism of this “parasites manipulation” effects have not been elucidated. Here, we reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…It is noteworthy that T. gondii infection is related to psychiatric disorders in some subclinical cases, as numerous studies have shown the correlation between schizophrenia and T. gondii infection ( Xiao et al., 2018 ). Chronic toxoplasmosis is an significant risk factor for schizophrenia, which might be attributed to the dysregulation of neuroendocrine and the neurotransmitter imbalance caused by chronic neuroinflammation, while psychiatric disorders also increase the exposure risk of T. gondii ( Yin et al., 2022 ).…”
Section: T Gondii Infection and Current Treatmentsmentioning
confidence: 99%
“…It is noteworthy that T. gondii infection is related to psychiatric disorders in some subclinical cases, as numerous studies have shown the correlation between schizophrenia and T. gondii infection ( Xiao et al., 2018 ). Chronic toxoplasmosis is an significant risk factor for schizophrenia, which might be attributed to the dysregulation of neuroendocrine and the neurotransmitter imbalance caused by chronic neuroinflammation, while psychiatric disorders also increase the exposure risk of T. gondii ( Yin et al., 2022 ).…”
Section: T Gondii Infection and Current Treatmentsmentioning
confidence: 99%
“…Neuroendocrine programs and neurotransmitter imbalance may act as the physiological basis for T. gondii induced psychiatric and behavioral disorders [71] .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine programs and neurotransmitter imbalance may act as the physiological basis for T. gondii induced psychiatric and behavioral disorders [71] . Glutamate (GLU) is the most abundant neurotransmitter in the brain, and its excitability plays a crucial role in brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…T. gondii infecting patients with behavioural disorders could possibly induce a “behavioural manipulation” in the host (e.g., reduction of fear, as revealed in animals with induced infection with T. gondii ). This affects the host transcription elements through epigenetic modifications and induction of special effectors (such as the Toxoplasma E2F4-associated EZH2-inducing Gene Regulator), resulting in a change in the host gene expression at both transcriptional and post-translational levels [ 120 ].…”
Section: Biological Alterations Underlying Suicidal Behaviourmentioning
confidence: 99%